Nonlinear absorption spectroscopy of a bis(Porphyrin)-substituted squaraine - Webster, S; Odom, SA; Padilha, L; Przhonska, O; Peceli, D; Hu, H; Nootz, G; Kachkovski, A; Matichak, J; Barlow, S; Anderson, H; Marder, SR; et al. (Optical Society of America, 2009)
The nonlinear absorption mechanisms of a bis(porphyrin)-substituted squaraine have been studied with femtosecond, picosecond, and nanosecond pulsewidths. The two-photon absorption is ~10× larger than those of the constituents and is explained by intra-molecular charge transfer. © 2009 Optical Society of America.